Calculation of winter average ten-day minimum flows of rivers of the Lake Sevan Basin and analysis of its time variability - Margaryan, Varduhi Gurgeni (Journal of the Belarusian State University. Geography and Geology, 2020)
Studying decadal minimum costs, especially in the context of expected climate change, is relevant and urgent. Both on the rivers of the study area and the whole republic, minimum water discharge is observed during periods of summer- autumn and winter low water. In both cases, the power of the rivers is mostly underground. However, summer-autumn rains can often disrupt the river’s feeding patterns and cause flooding. The paper calculated the winter average ten-day minimum costs for posts that have a long series of observations on rivers flowing into Lake Sevan. In a number of longterm observations, the dynamics of changes in the winter average ten-day minimum costs of rivers flowing into the basin and the patterns of their spatial distribution have been estimated. As a source material daily data from actual observations at 12 hydrological posts in the study area of the Service of the Hydrometeorology and Active Influence on Atmospheric Phenomena, Ministry of Emergency Situations of the Republic of Armenia, are used. All observed hydrological posts have a number of observations 40 years or more. The methods used in the work are: mathematical-statistical, extrapolation, interpolation, analysis, analogue and correlation. It turned out that most rivers in the Lake Sevan Basin have a tendency to increase in winter average ten-day minimum costs.
Keywords: coefficient of variability; coefficient of irregularity; security; dynamics; minimal costs; Lake Sevan Basin